Dysbaric osteonecrosis in masters and instructors experienced dive - (:unkn) unknown (AEROSPACE MEDICAL ASSOC, 2007)
Introduction: Dysbaric osteonecrosis (DON) is a type of aseptic bone necrosis of long bones such as the humerus, femur, and tibia. It is observed in workers who perform in high-pressure environments. Methods: There were 58 volunteer divers included in this study who had performed at least 500 dives, were working as a dive master or instructor, had never performed industrial and commercial dives, and did not have a diagnosis of osteonecrosis. Radiological evaluation was performed according to the guidelines suggested by The British Research Council Decompression Sickness Panel. A total of eight X-rays were taken per patient. When suspicious lesions were detected, MRI of the region was performed. Results: Of the 58 divers, 2 were eliminated because of inadequate X-ray studies. A total of 18 DON lesions were detected in 14 of 56 (25%) divers. Age was the only variable independently associated with the development of DON (P < 0.05). Discussion: The DON prevalence of 25% in this study is high considering the dive instructors had thorough diving training and strictly practiced the decompression rules. We believe this high prevalence is a result of frequent and sometimes deep dives for many years. Our findings raise the question of whether these divers can be seen as sports divers or should be seen as occupational divers. if the latter description is approved, dive masters and instructors should be kept under periodic screening for DON lesions just like professional commercial divers to help reduce the morbidity associated with this disease.
Keywords: DON; radiology; screening; SCUBA-DIVER